Retracted: A comparative study of propranolol versus amitriptyline at a low dose for prophylaxis of episodic migraine at a tertiary care centre - Banu, Nasra; Shaifali, Iram; Chandra, Shalini; Saxena, Anju (International Journal of Basic & Clinical Pharmacology, 2024)
The article "A comparative study of propranolol versus amitriptyline at a low dose for prophylaxis of episodic migraine at a tertiary care centre" has been retracted by the Editor-in-Chief due to violations of the policies and practices of the International Journal of Basic & Clinical Pharmacology. The retraction follows a complaint from the study institution regarding the presentation of false information in the study details, issues with ethical approval, and discrepancies in authorship.